2023
DOI: 10.1021/acs.jmedchem.3c01634
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Degradation of PCSK9 In Vivo by Autophagy-Tethering Compounds

Zhirong Ouyang,
Muye Ma,
Ziwen Zhang
et al.

Abstract: Proprotein convertase subtilisin/kexin type-9 (PCSK9), a secreted protein that is synthesized and spontaneously cleaved in the endoplasmic reticulum, has become a hot lipidlowering target chased by pharmaceutical companies in recent years. Autophagosome-tethering compounds (ATTECs) represent a new strategy to degrade targeted biomolecules. Here, we designed and synthesized PCSK9•ATTECs that are capable of lowering PCSK9 levels via autophagy in vivo, providing the first report of the degradation of a secreted p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…17 Similarly, Zhao, Guo, Gu, and coworkers found that changes in the linker structure within their PCSK9 ATTEC compounds resulted in an increase in binding to LC3B from 9.88 μM to 5.69 μM. 22 Given our results, it is possible that positive contributions to binding by the linker attached to the C11 hydroxyl or oxindole amide compensates for the decrease in binding to LC3/GABARAP proteins caused by substitution at these positions.…”
Section: Figuresupporting
confidence: 56%
See 3 more Smart Citations
“…17 Similarly, Zhao, Guo, Gu, and coworkers found that changes in the linker structure within their PCSK9 ATTEC compounds resulted in an increase in binding to LC3B from 9.88 μM to 5.69 μM. 22 Given our results, it is possible that positive contributions to binding by the linker attached to the C11 hydroxyl or oxindole amide compensates for the decrease in binding to LC3/GABARAP proteins caused by substitution at these positions.…”
Section: Figuresupporting
confidence: 56%
“…17 More recently, Gu and coworkers reported an ATTEC that incorporated 1 to degrade the protein PCSK9 as a potential atherosclerosis therapy. 22 Similarly, Dong and coworkers recently described an ATTEC using 1 to degrade PDEδ, an emerging target for pancreatic cancer therapy. 29…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Autophagosome-tethering compounds (ATTECs) have emerged as a new technology in targeted protein degradation. As a heterobifunctional molecule, ATTECs recruit the protein of interest (POI) to autophagy key protein LC3 in the phagophore membrane and subsequently induce POI degradation through the autophagy lysosomal pathway. ATTECs can thus disrupt the enzymatic and nonenzymatic functions of the kinase by depleting its scaffold.…”
Section: Introductionmentioning
confidence: 99%